A Low Complexity Channel Estimation and Detection for Massive MIMO Using SC-FDE - Marques da Silva, Mário (2020)
Funding Information: We acknowledge the support of FCT/MCTES, as described above in funding. Funding Information: This work is funded by FCT/MCTES through national funds and when applicable co-funded EU funds under the project UIDB/EEA/50008/2020. Acknowledgments Publisher Copyright: © 2020 by the authors.